Synthesis of azimic acid using hydroformylation - Bates, Roderick Wayland (2013)
A synthesis of the alkaloid azimic acid has been achieved using double hydroformylation with a single tandem condensation to form the six membered ring. The oxygen substituent was introduced by diastereoselective dihydroxylation, cis to the existing alkyl substituent. The methyl substituent was introduced via an iminium ion intermediate under stereoelectronic control.